Penerapan Metode Pembelajaran Bermain Jawaban Dalam Keterampilan Membaca Bahasa Jerman - Telly Trie Utami; Mantasiah R; Syamsu Rijal (Phonologie : Journal of Language and Literature, 2021)
Abstract. This research aims to improve German language reading skills of 11th grade students of State Senior High School 1 Gowa by using Playing answer learning method. The subject in this research are the students of 11th grade of Mathematics and Natural Science 6 of State Senior High School 1 Gowa. This research is a type of classroom action research which consists of two cycles. The data of this research consist of qualitative and quantitative data. Qualitative data are the data which describe the learning process obtained through observation. While, quantitative data are the data obtained from the results of cycle I and cycle II tests. The results of the research showed that the learning outcomes of students reading skills increased, namely 73.52% in the cycle I and increased to 92.20% in the cycle II. This results indicated that the implementation of Playing answer learning method can improve German language reading skills of 11th grade students of State Senior High School 1 Gowa.